Choice of contraceptive method after surgical artificial abortion and evaluation of their effectiveness (Literature Review) - Hamrayeva Madina; Abdullaeva L.M (Genius Journals, 2024)
Abortion is one of the frequent causes of gynecologic diseases and impaired fertility. More than 10-15%, and according to G.P. Parafeinik et al. and I.B. Frolov (2008), 21.7% of women after abortion have gynecological diseases, almost half of the women who underwent this operation, aggravated chronic inflammatory processes of the genital sphere. The greatest danger is undoubtedly an infected abortion. If the infection spreads, salpingoophoritis may develop, the frequency of which, according to various authors, ranges from 3.5 to 5.7%, metoendometritis - 1.7-3%, parametritis - 1.34%, as well as metritis, pelvic peritonitis, thrombophle- uterine venous thrombophlebitis and many other post-abortion infectious diseases. In addition, fetal egg retention (1.27-5.7%), ICH (0.13%), menstrual irregularities (11.4%) and other pathologies are common complications. According to Schulze and Herold (2008), endometritis complicated the course of the post-abortion period in 1.58% of women. A study of the long-term consequences of induced abortion revealed its negative impact on fertility. The study of the long-term consequences of induced abortion revealed its negative impact on fertility: the possibility of secondary infertility, tubal pregnancy, spontaneous abortions, and habitual pregnancy failure.
Keywords: Endometritis; infertility; contraceptive methods